Distributed cooperative control of consistency of hydraulic support robot group moving frame - Mingze SUN; Yongqiang WANG; Yajun CHANG; Desheng ZHU; Shiyan LI; Kehu YANG (Meitan xuebao)
As the main equipment of coal mining face's propulsion and support, the consistency of hydraulic support directly affects the flatness of coal mining face, and then affects the operation safety and mining efficiency. At present, the hydraulic support system mainly adopts centralized control mode, and once the central controller fails, it will seriously affect the normal operation of the system. The hydraulic support is regarded as an intelligent individual with independent perception, decision-making ability and control ability, and a decentralized distributed cooperative support moving control method is proposed. Firstly, combined with the mechanical structure of the support, the mathematical model of the single moving mechanism of the hydraulic support is analyzed and established, and an adaptive communication topology construction method based on state information is designed. Secondly, according to the proposed communication topology, the consistency control protocol is formulated, and the distributed extended state observer and disturbance feedback loop are designed to estimate the unknown disturbance and actively cancel the disturbance at the output, thus improving the robustness of the consistency control algorithm. Finally, the feasibility of the consistency control algorithm is verified by Amesim-Simulink co-simulation. By comparing with PID, the control accuracy and active anti-disturbance ability of the algorithm are analyzed, and the feasibility and stability of the two common methods of staggered frame moving and group sequential frame moving are simulated and verified. The results show that the distributed cooperative control method proposed can realize the functions of automatic moving and self-straightening of hydraulic support groups under various complex disturbances. Compared with the PID centralized control method commonly used in engineering, it has the advantages of high reliability, good consistency, strong active anti-interference ability and good expansibility, and can adjust the control strategy independently to adapt to various moving modes, thus improving the efficiency and safety of moving supports.